Stage‐dependent nigral neuronal loss in incidental Lewy body and Parkinson's disease. Issue 10 (3rd July 2014) - Dijkstra, Anke A.; Voorn, Pieter; Berendse, Henk W.; Groenewegen, Henk J.; Netherlands Brain Bank; Rozemuller, Annemieke J.M.; van de Berg, Wilma D.J.
Abstract To gain a better understanding of the significance of α‐synuclein pathological conditions during disease progression in Parkinson's disease, we investigated whether 1) nigral neuronal loss in incidental Lewy body disease and Parkinson's disease donors is associated with the local burden α‐synuclein pathological conditions during progression of pathological conditions; 2) the burden and distribution of α‐synuclein pathological conditions are related to clinical measures of disease progression. Post‐mortem tissue and medical records of 24 Parkinson's disease patients, 20 incidental Lewy body disease donors, and 12 age‐matched controls were obtained from the Netherlands Brain Bank for morphometric analysis. We observed a 20% decrease in nigral neuronal cell density in incidental Lewy body disease compared with controls. Nigral neuronal loss (12%) was already observed before the appearance α‐synuclein aggregates. The progression from Braak α‐synuclein stage 3 to 4 was associated with a significant decline in neuronal cell density (46%). Nigral neuronal loss increased with later Braak α‐synuclein stages but did not vary across consecutive Braak α‐synuclein stages. We observed a negative correlation between neuronal density and local α‐synuclein burden in the substantia nigra of Parkinson's disease patients (ρ = −0.54), but no relationship with Hoehn & Yahr stage or disease duration. In conclusion, our findings cast doubt on the pathogenic role of α‐synuclein aggregates in elderly, but do suggest that the severity of neurodegeneration and local burden of α‐synuclein pathological conditions are closely coupled during disease progression in Parkinson's disease. © 2014 International Parkinson and Movement Disorder Society